(untitled) (YURISPRUDENSIYA, 2026)
This article examines the specific aspects and significance of mediation in resolving family disputes, mechanisms for reliable protection of the rights and freedoms of the parties involved in family disputes, the advantages of mediation over litigation, as well as the experience of foreign countries and the opinions of foreign and domestic legal scholars. In the study, especially using historical and comparative methods, the long-standing existence of the institution of mediation in our country was analyzed. Existing gaps in national legislation and issues of their improvement were also considered. The positive and negative aspects of the mediator’s participation were identified. The article examines in detail the significance and essence of mediation in resolving family disputes, as well as the advantages of resolving family disputes through alternative and expedited methods. In addition, a comparative analysis of national legislation on mediation in resolving family disputes with the legislation and practice of foreign countries, in particular, the United States of America, Great Britain, Germany, Austria, the Russian Federation, Ukraine, Belarus, Kazakhstan, and Kyrgyzstan, was conducted. The article draws scientific and theoretical conclusions and develops practical proposals and recommendations for improving mediation in family disputes.